Device Discovery in the Smart Home Environment - Ahmed, Nurzaman (2024)
With the availability of Internet of Things (IoT) devices offering varied services, smart home environments have seen widespread adoption in the last two decades. Protecting privacy in these environments becomes an important problem because IoT devices may collect information about the home's occupants without their knowledge or consent. Furthermore, a large number of devices in the home, each collecting small amounts of data, may, in aggregate, reveal non-obvious attributes about the home occupants. A first step towards addressing privacy is discovering what devices are present in the home. In this paper, we formally define device discovery in smart homes and identify the features that constitute discovery in that environment. Then, we propose an evaluative rubric that rates smart home technology initiatives on their device discovery capabilities and use it to evaluate four commonly deployed technologies. We find none cover all device discovery aspects. We conclude by proposing a combined technology solution that provides comprehensive device discovery tailored to smart homes.